2014
DOI: 10.1007/s11427-014-4656-8
|View full text |Cite
|
Sign up to set email alerts
|

Puzzle out the regulation mechanism of PI4KIIα activity

Abstract: Phosphatidylinositol 4-kinase II (PI4KII), the most abundant PI4K in mammalian cells, is best known for its essential role in providing the substrate for phosphatidylinositol 3-kinase (PI3K), an important kinase for phospholipid signaling. PI4KII also plays important roles in membrane trafficking, phagocytosis and the exo-endocytic cycle of synaptic vesicles. Its dysfunction results in tumor growth, spastic paraplegia and Gaucher's disease. Therefore, PI4KII may potentially be an important drug target.The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…However, mutations or deletions in the PI-binding regulation region (for example, the palmitoylation insertion, D165-173, or K165E/K168E/K172E), but not those at the nucleotidebinding site (for example, K152A, D346A), reduced the DT m value. We previously reported that the palmitoylation insertion modulates kinase activity by tuning the PI-binding pocket (26,38), and these results confirm that PI-273 is a PI-competitive inhibitor of PI4KIIa.…”
Section: Pi-273 Is a Pi-competitive Inhibitor Of Pi4kiiasupporting
confidence: 70%
“…However, mutations or deletions in the PI-binding regulation region (for example, the palmitoylation insertion, D165-173, or K165E/K168E/K172E), but not those at the nucleotidebinding site (for example, K152A, D346A), reduced the DT m value. We previously reported that the palmitoylation insertion modulates kinase activity by tuning the PI-binding pocket (26,38), and these results confirm that PI-273 is a PI-competitive inhibitor of PI4KIIa.…”
Section: Pi-273 Is a Pi-competitive Inhibitor Of Pi4kiiasupporting
confidence: 70%
“…It is well documented that proteins can regulate the physical properties and/or shape of the biological membranes [42][43][44][45]. However, the structural and functional analysis of PI4K IIα suggests that in fact the membrane regulates the activity of PI4K IIα enzyme [46][47][48]. Zhou and colleagues [46,47] suggest that the fluidity of the membrane (i.e.…”
Section: Type II Pi4ksmentioning
confidence: 99%
“…However, the structural and functional analysis of PI4K IIα suggests that in fact the membrane regulates the activity of PI4K IIα enzyme [46][47][48]. Zhou and colleagues [46,47] suggest that the fluidity of the membrane (i.e. the cholesterol content) regulate its activity.…”
Section: Type II Pi4ksmentioning
confidence: 99%
“…PI4K family II includes PI4KIIA and PI4KIIB. 8 Among them, PI4KIIA, located at chromosome 10 q24.2, is the most abundant PI4K protein in mammals, mainly present in trans‐Golgi network and endonucleosomes, 9 , 10 and involved in targeting trans‐Golgi network and intracellular transport. 11 , 12 , 13 Previous researchers have shown that PI4KIIA can regulate HIF‐1alpha through the HER‐2/PI3K and ERK cascades, thus participating in tumorigenesis and progression.…”
Section: Introductionmentioning
confidence: 99%
“…PI4K family II includes PI4KIIA and PI4KIIB 8 . Among them, PI4KIIA, located at chromosome 10 q24.2, is the most abundant PI4K protein in mammals, mainly present in trans‐Golgi network and endonucleosomes, 9,10 and involved in targeting trans‐Golgi network and intracellular transport 11–13 .…”
Section: Introductionmentioning
confidence: 99%